The PerioGene North study reveals that periodontal inflammation and advanced jawbone loss in periodontitis associate with serum gingipain antibodies but not with systemic autoimmunity - Kindstedt, Elin; de Vries, Charlotte; Wänman, Magnus; Potempa, Barbara Aleksandra; Potempa, Jan; Lindquist, Susanne; Esberg, Anders; Lundberg, Karin; Lundberg, Pernilla (Frontiers in Immunology, 2025)
IntroductionPeriodontitis is associated with rheumatoid arthritis (RA). One hypothesis posits that this connection arises from the formation of autoantibodies against citrullinated proteins (ACPA) in inflamed gums, possibly triggered by Porphyromonas gingivalis. We previously demonstrated an increased antibody response to P. gingivalis arginine gingipains (anti-Rgp IgG), not only in individuals with severe periodontitis compared to controls, but in RA versus controls, with an association to ACPA. In the present study, we set out to further explore the relationship between anti-Rgp IgG, ACPA and periodontitis, including clinical periodontal parameters, in the large and well-characterized PerioGene North case-control study.MethodsWe measured serum levels of anti-Rgp and ACPA IgG by enzyme-linked immunosorbent assay (ELISA), in 478 patients with periodontitis and 509 periodontally healthy controls within PerioGene North. Subsequently, anti-Rgp IgG levels and ACPA status were analysed in relation to periodontitis and clinical periodontal parameters.ResultsSerum anti-Rgp IgG levels were elevated in cases versus controls (p< 0.001). However, receiver operating characteristic (ROC) curve analysis revealed that anti-Rgp IgG could not efficiently discriminate cases from controls (AUC= 0.63; 95% CI: 0.60 – 0.66). Among cases, increased anti-Rgp IgG levels associated with high periodontal inflammation and advanced alveolar bone loss (p<0.001 for both). An ACPA response was detected in 15 (3.1%) cases and 6 (1.2%) controls (p=0.033), but no association to periodontitis was evident after adjustment for age and smoking and anti-Rgp IgG levels did not differ between ACPA-positive and ACPA-negative individuals.ConclusionWe show that anti-Rgp IgG identifies a subgroup of periodontitis patients with high degree of periodontal inflammation and advanced alveolar bone loss, but we do not find support for a link between periodontitis or anti-Rgp IgG and ACPA status in PerioGene North. Given the association between anti-Rgp and alveolar bone loss, the mechanistic role of gingipains in bone resorption should be experimentally explored.